(untitled) (Annals of Medical Research, 2021)
Aim: Breast hamartomas are uncommon benign lesions that constitute 4.8% of benign breast tumors; they consist of mammary ducts and lobules, fatty tissue, and fibrous tissue. The aim of this study was to determine the clinical and pathological characteristics of breast hamartomas diagnosed by surgical resection and to examine the accompanying lesions. Material and Methods: Patients who underwent breast surgery between January 2013 and January 2018 at Konya Education and Research Hospital and who were diagnosed as having breast hamartomas were reviewed retrospectively. Results: Seven breast hamartomas were identified. All of them were female. The mean age was 45 years. The mean tumor size was 3.9 cm. Most of the lesions were located in the right breast (57.1%). All the hamartomas appeared in the upper part of the breast. Five of the seven cases were admitted with a painless palpable mass in the breast (71.4%). Three of the seven cases were myoid hamartomas. The type of lesion most commonly associated with breast hamartomas is cyst formation. Pseudoangiomatous stromal hyperplasia, columnar cell hyperplasia, and ductal epithelial hyperplasia are also common. Ductal epithelial hyperplasia and columnar cell hyperplasia were observed in all the myoid hamartomas. Ductal carcinoma in situ was detected in one case; it was also a myoid hamartoma. Conclusions: Breast hamartomas are accompanied by many types of lesions such as fibrocystic changes, adenosis, ductal epithelial hyperplasia, and pseudoangiomatous stromal hyperplasia. In addition to these lesions, columnar cell hyperplasia was also identified. Malignancies are rarely detected in breast hamartomas; however, one case of ductal carcinoma in situ in a myoid hamartoma was detected.